Diseño de una Microred híbrida soportada en un tráiler comercial para una vivienda promedio en la Isla de Providencia, Colombia (2024)
This work proposes the design of a mobile microgrid under renewable energy sources (solar-photovoltaic and wind), which provides an autonomous and efficient energy solution for an average home on the Island of Providencia, belonging to the Archipelago of San Andrés, Providencia and Santa Catalina, identified as a Non-Interconnected Zone (ZNI) in Colombia. The problem covered by this research corresponds to the dependence that the island has on marine diesel as fuel for the electric power generation plants and the freight involved in transporting said fuel from the Cartagena plant, given the inability of the island to supply itself. of the National Interconnected System; in addition to the environmental impact generated by burning diesel. However, the island has great solar and wind potential.